2008
DOI: 10.1093/icesjms/fsn067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hook size and barbless hooks on hooking injury, catch per unit effort, and fish size in a mixed-species recreational fishery in the western Mediterranean Sea

Abstract: Alós, J., Palmer, M., Grau, A. M., and Deudero, S. 2008. Effects of hook size and barbless hooks on hooking injury, catch per unit effort, and fish size in a mixed-species recreational fishery in the western Mediterranean Sea. – ICES Journal of Marine Science, 65: 899–905. The effects of hook size (small vs. large) and type (conventional vs. barbless) on hooking injury, catch per unit effort (cpue), and fish size in a mixed-species recreational fishery in the Balearic Islands (western Mediterranean) are evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 31 publications
6
68
2
2
Order By: Relevance
“…The difference in the catch rates of Spotted Rose Snapper between #10 and #8 hooks cannot be explained simply as an increase in the catch of smaller fish, though, since size selectivity between these hooks was not observed. One explanation may be that smaller hooks are more likely to be swallowed and therefore hooked more deeply in the body (Alós et al 2008b), reducing the likelihood of a fish escaping. Our analysis revealed that the catch rates of 11 additional fish species, one fish genus, and various species of echinoderms (seastars) were also inversely proportional to hook size (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in the catch rates of Spotted Rose Snapper between #10 and #8 hooks cannot be explained simply as an increase in the catch of smaller fish, though, since size selectivity between these hooks was not observed. One explanation may be that smaller hooks are more likely to be swallowed and therefore hooked more deeply in the body (Alós et al 2008b), reducing the likelihood of a fish escaping. Our analysis revealed that the catch rates of 11 additional fish species, one fish genus, and various species of echinoderms (seastars) were also inversely proportional to hook size (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Circle hooks could maintain or even increase the catch rates of the target species (Løkkeborg and Bjordal 1992;Woll et al 2001), especially for those species that tend to be hooked in the mouth (Løkkeborg and Bjordal 1992). In addition, circle hooks could reduce the mortality of released fish (Alós et al 2008b). If fishers were to adopt a slot limit, circle hooks could allow large and small fish to be released with less injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disisi lain, upaya meningkatkan efektivitas penangkapan diharapkan dapat terjadi, sehingga produktivitas penangkapan ikan dapat ditingkatkan. Teknologi pancing ulur yang masih sangat sederhana, dimungkinkan untuk memodifikasi alat tangkap untuk meningkatkan produksi dengan mempertimbangkan bukaan mulut dan panjang badan dari ikan target atau menambah upaya yang selektif dan ramah lingkungan (Alo's et al 2008). Berdasarkan hasil penelitian Ralston (1982) bahwa penggunaan ukuran mata pancing yang lebih besar memberikan ukuran hasil tangkapan yang lebih besar yakni sebesar 71% dibandingkan dengan ukuran mata pancing yang kecil hanya sebesar 29%.…”
Section: Analisis Matriks Swotunclassified
“…There is some evidence that catch-and-release mortality rates are strongly influenced by the biological characteristics of the target species (Muoneke and Childress, 1994). However, certain other factors, such as the body part of the fish that was hooked (Pope et al, 2007;Alós et al, 2008), the type of bait (Reeves and Bruesewitz, 2007) and the fighting and handling time (Cooke and Suski, 2004) could also be determinants of mortality rate. Broadhurst et al (2005), studying the mortality rate of the main target species of Australian estuary sport fishing, reported mortality rates between 0 and 36.6% and found that the body part hooked and the time taken to release the fish were the main factors influencing mortality.…”
Section: Introductionmentioning
confidence: 99%